Novel porous silica encapsulated Au nanoreactors as peroxidase mimic for one-pot glucose detection - Samanta, Anupam; Dhar, Basab B.; Devi, R. Nandini (New Journal of Chemistry, 2012)
The peroxidase family of natural enzymes facilitate H2O2 reduction by one electron transfer through aromatic substrates, if chromogenic, they can be used in the colorimetric detection of H2O2 and subsequently glucose in tandem with glucose oxidase. Au nanoparticles encapsulated within porous silica exhibited peroxidase mimetic activity and kinetic parameter evaluation indicates an excellent affinity for H2O2. It is also shown to have a detection capability for glucose in very low concentrations and could be used for glucose detection in a one-pot assay. The material is synthesised by using cation-ended thiol-stabilised ultra small gold clusters as precursors. Removal of the thiols creates micropores within the silica, making this material unique in that the active centres are protected inside the silica, yet are accessible to reactant molecules. This characteristic makes the material ideal as a detection tool where attrition resistance will be advantageous.

One pot glucose detection by [Fe-III(biuret-amide)] immobilized on mesoporous silica nanoparticles: an efficient HRP mimic - Malvi, Bharmana; Panda, Chakadola; Dhar, Basab B.; Sen Gupta, Sayam (Chemical Communications, 2012)
An [Fe-III(biuret-amide)] complex has been immobilized onto mesoporous silica nanoparticles via Cu(I) catalyzed azide-alkyne click chemistry. This hybrid material functions as an efficient peroxidase mimic and was successfully used for the quantitative determination of hydrogen peroxide and glucose via a one-pot colorimetric assay.

Ultrasmall gold cluster arrays encapsulated in silica nanospheres: applications in fluorescence imaging and catalysis - Samanta, Anupam; Dhar, Basab B.; Devi, R. Nandini (Journal of Physical Chemistry C, 2012)
Facile synthesis of ultrasmall gold nanoclusters of size <2 nm dispersible in water using a novel quaternary ammonium ligand is reported. Further, arrays of these nanoclusters are encapsulated in monodisperse silica nanospheres of size 25-30 nm. The photophysical characteristics of the clusters are found to be intact upon encapsulation, rendering the resulting composite material ideal for fluorescence imaging applications. We have further shown the utilization of these materials in catalysis as precursors for Au nanopartides encapsulated in porous silica.

Catalytic signal amplification using [Fe-III(biuret-amide)]-mesoporous silica nanoparticles: visual cyanide detection - Panda, Chakadola; Dhar, Basab B.; Malvi, Bharmana; Bhattacharjee, Yudhajit; Sen Gupta, Sayam (Chemical Communications, 2013)
Catalytic signal amplification was used for the colorimetric detection of CN- in aqueous media by using the enzyme catalase in tandem with mesoporous silica nanoparticle based synthetic HRP enzyme mimic Fe-MSNs. Signal amplification up to a maximum of eight fold was observed for the reporter ``oxidized TMB'' with respect to the added CN- ion.

Development of a multifunctional catalyst for a ``relay'' reaction - Ganai, Anal Kumar; Shinde, Pravin; Dhar, Basab B.; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (RSC Advances, 2013)
In the area of catalysis, nanoparticles and enzymes are two of the most important systems. By amalgamating the two, we present here proof of the concept that it is possible to prepare a multifunctional catalyst that can carry out a ``relay'' reaction. The catalyst consists of a surface bound enzyme on a metal(core)-silica(shell) nanoparticle architecture. Here the enzyme catalyzes the 1st reaction and the metal nanoparticles act as a catalyst for the 2nd reaction of the product from the 1st reaction. In particular, we have studied the catalytic activity of glucosidase grafted Au@mSiO(2) on 4-nitrophenyl-beta-glucopyranoside, where glucosidase will catalyse the 1st step to generate 4-nitrophenol, which acts as a substrate for the next reduction step which is catalysed by the Au nanoparticles present inside the mesoporous silica shell.

Fe-TAML encapsulated inside mesoporous silica nanoparticles as peroxidase mimic: femtomolar protein detection - Kumari, Sushma; Dhar, Basab B.; Panda, Chakadola; Meena, Abhishek; Sen Gupta, Sayam (ACS Applied Materials & Interfaces, 2014)
Peroxidase, such as horseradish peroxidase (HRP), conjugated to antibodies are routinely used for the detection of proteins via an ELISA type assay in which a critical step is the catalytic signal amplification by the enzyme to generate a detectable signal. Synthesis of functional mimics of peroxidase enzyme that display catalytic activity which far exceeds the native enzyme is extremely important for the precise and accurate determination of very low quantities of proteins (fM and lower) that is necessary for early clinical diagnosis. Despite great advancements, analyzing proteins of very low abundance colorimetrically, a method that is most sought after since it requires no equipment for the analysis, still faces great challenges. Most reported HRP mimics that show catalytic activity greater than native enzyme (similar to 40-fold) are based on metal/metal-oxide nanoparticles such as Fe3O4. In this paper, we describe a second generation hybrid material developed by us in which approximately 25 000 alkyne tagged biuret modified Fetetraamido macrocyclic ligand (Fe-TAML), a very powerful small molecule synthetic HRP mimic, was covalently attached inside a 40 nm mesoporous silica nanopartide (MSN). Biuret-modified Fe-TAMLs represent one of the best small molecule functional mimics of the enzyme HRP with reaction rates in water close to the native enzyme and operational stability (pH, ionic strength) far exceeding the natural enzyme. The catalytic activity of this hybrid material is around 1000-fold higher than that of natural HRP and 100-fold higher than that of most metal/metal oxide nanoparticle based HRP mimics reported to date. We also show that using antibody conjugates of this hybrid material it is possible to detect and, most importantly, quantify femtomolar quantities of proteins colorimetrically in an ELISA type assay. This represents at least 10-fold higher sensitivity than other colorimetric protein assays that have been reported using metal/metal oxide nanoparticles as HRP mimic. Using a human IgG expressing cell line, we were able to demonstrate that the protein of interest human IgG could be detected from a mixture of interfering proteins in our assay.
Keywords: colorimetrically; immuno assay; MSN; peroxidase mimic; signal amplification

Formation of a room temperature stable Fe-V(O) complex: reactivity toward unactivated C-H bonds - Ghosh, Munmun; Singh, Kundan K.; Panda, Chakadola; Weitz, Andrew; Hendrich, Michael P.; Collins, Terrence J.; Dhar, Basab B.; Sen Gupta, Sayam (Journal of American Chemical Society, 2014)
An Fe-V(O) complex has been synthesized from equimolar solutions of (Et4N)(2)[Fe-III(Cl)(biuretamide)] and mCPBA in CH3CN at room temperature. The Fe-V(O) complex has been characterized by UV-vis, EPR, Mossbauer, and HRMS and shown to be capable of oxidizing a series of alkanes having C-H bond dissociation energies ranging from 99.3 kcal mol(-1) (cyclohexane) to 84.5 kcal mori (cumene). Linearity in the Bell-Evans-Polayni graph and the finding of a large kinetic isotope effect suggest that hydrogen abstraction is engaged the rate-determining step.

Homogeneous photochemical water oxidation by biuret-modified Fe-TAML: evidence of Fe-V(O) intermediate - Panda, Chakadola; Debgupta, Joyashish; Diaz, David Diaz; Singh, Kundan K.; Gupta, Sayam Sen; Dhar, Basab B. (Journal of the American Chemical Society, 2014)
{Water splitting, leading to hydrogen and oxygen in a process that mimics natural photosynthesis, is extremely important for devising a sustainable solar energy conversion system. Development of earth-abundant, transition metal-based catalysts that mimic the oxygen-evolving complex of photosystem II, which is involved in oxidation of water to O-2 during natural photosynthesis, represents a major challenge. Further, understanding the exact mechanism, including elucidation of the role of active metal-oxo intermediates during water oxidation (WO), is critical to the development of more efficient catalysts. Herein, we report Fe-III complexes of biuret-modified tetra-amidomacrocyclic ligands (Fe-TAML; 1a and 1b) that catalyze fast, homogeneous, photochemical WO to give OD with moderate efficiency (maximum TON = 220

Encapsulation of ultra small metal clusters in silica: evolution of the concept of nanoreactors and the case of Ag-Pd@SiO2 alloy catalyst - Mondal, Sourik; Samanta, Anupam; Dhar, Basab B.; Devi, R. Nandini (Catalysis Today, 2015)
The concept of encapsulation of ultra small clusters within silica evolved as a means to address the sintering of active metal nanoparticles and subsequent deactivation observed in supported noble metal catalysts. It is hypothesised that sintering, which mainly occurs due to mobility of metal species on the support surfaces, can be minimised if the growth and movement of metal nanoparticles are constrained. First, nanoparticles are isolated inside 1D channels in 2D mesoporous compounds and the idea develops to complete encapsulation of thiol protected ultra small nanoclusters in silica spheres. Sintering is better controlled in the latter due to the confined space for growth of nanoparticles. Access of reactant molecules to the active metal surfaces also is ensured by porosity created in the silica matrix forming the basis of the concept of nanoreactors. In this paper, we elaborate on the evolution of this concept from our earlier work on highly sinter resistant silica encapsulated Au, Pd and Au-Pd alloys to the present system of Ag-Pd alloy encapsulated in silica. Silver, with the lowest Tammann temperature among noble metals, is highly prone to sintering which is adequately controlled by alloying with Pd as well as encapsulation in silica. Its enhanced activity in paranitrophenol reduction in comparison with pure metals indicates the advantageous effect of alloying. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ag-Pd alloy; Encapsulation; Sinter resistant; Sintering; Ultra small nanoclusters

Mechanism of alcohol oxidation by Fe-V(O) at room temperature - Ghosh, Munmun; Nikhil, Y. L. K.; Dhar, Basab B.; Sen Gupta, Sayam (Inorganic Chemistry, 2015)
{Selective oxidation of alcohol to its corresponding carbonyl compound is an important chemical process in biological as well as industrial reactions, The heme containing enzyme CytP450 has been known to selectively oxidize akohols to their corresponding carbonyl compounds. The mechanism of this reaction, which involves high-valent Fe-IV(O)-porphyrin(center dot+) intermediate with alcohol, has been well-studied extensively both with the native enzyme and with model complexes. In this paper, we report for the first time the mechanistic insight of, alcohol oxidation with Fe-V(O) complex of biuret TAML (bTAML), Which is isoelectronic with Fe-IV(O)-porphyrin(center dot+) intermediate form in CytP450. The oxidations displayed saturation kinetics, which allowed us to determine both the binding constants and first-order rate constants for the reaction. The K and k values observed for thel oxidation of benzyl alcohol by Fe-V(O) at room temperature (K = 300 M-1

Mechanism of oxygen atom transfer from Fe-V(O) to olefins at room temperature - Singh, Kundan K.; Tiwari, Mrityunjay K.; Dhar, Basab B.; Vanka, Kumar; Sen Gupta, Sayam (Inorganic Chemistry, 2015)
In biological oxidations, the intermediate Fe-V(0)(OH) has been proposed to be the active species for catalyzing the epoxidation of alkenes by nonheme iron complexes. However, no study has been reported yet that elucidates the mechanism of direct O-atom transfer during the reaction of Fe-V(0) with alkenes to form the corresponding epoxide. For the first time, we study the mechanism of O-atom transfer to alkenes using the Fe-V(0) complex of biuret-modified Fe-TAML at room temperature. The second-order rate constant (k(2)) for the reaction of different alkenes with Fe-V(0) was determined under single-turnover conditions. An 8000-fold rate difference was found between electron-rich (4-methoxystyrene; k(2) = 216 M-1 s(-1)) and electron-deficient (methyl transcinnamate; k(2) = 0.03 M-1 s(-1)) substrates. This rate difference indicates the electrophilic character of Fe-V(0). The use of cis-stilbene as a mechanistic probe leads to the formation of both cis- and trans-stilbene epoxides (73:27). This suggests the formation of a radical intermediate, which would allow C-C bond rotation to yield both stereoisomers of stilbene-epoxide. Additionally, a Hammett rho value of -0.56 was obtained for the para-substituted styrene derivatives. Detailed DFT calculations show that the reaction proceeds via a two-step process through a doublet spin surface. Finally, using biuret-modified Fe-TAML as the catalyst and NaOCl as the oxidant under catalytic conditions epoxide was formed with modest yields and turnover numbers.

Electrochemical formation of Fe-V (O) and mechanism of its reaction with water during O-O bond formation - Pattanayak, Santanu; Chowdhury, Debarati Roy; Garai, Bikash; Singh, Kundan K.; Paul, Amit; Dhar, Basab B.; Sen Gupta, Sayam (Chemistry-A European Journal, 2017)
A detailed electrochemical investigation of a series of iron complexes (biuret-modified tetraamido iron macrocycles FeIII-bTAML), including the first electrochemical generation of Fe-V(O), and demonstration of their efficacy as homogeneous catalysts for electrochemical water oxidation (WO) in aqueous medium are reported. Spectroelectrochemical and mass spectral studies indicated FeV(O) as the active oxidant, formed due to two redox transitions, which were assigned as Fe-IV(O)/Fe-III(OH2)and Fe-V(O)/Fe-IV(O). The spectral properties of both of these high-valent iron oxo species perfectly match those of their chemically synthesised versions, which were thoroughly characterised by several spectroscopic techniques. The O-O bond-formation step occurs by nucleophilic attack of H2O on FeV(O). A kinetic isotope effect of 3.2 indicates an atom-proton transfer (APT) mechanism. The reaction of chemically synthesised Fe-V(O) in CH3CN and water was directly probed by electrochemistry and was found to be first-order in water. The pK(a) value of the buffer base plays a critical role in the rate-determining step by increasing the reaction rate several-fold. The electronic effect on redox potential, WO rates, and onset overpotential was studied by employing a series of iron complexes. The catalytic activity was enhanced by the presence of electron-withdrawing groups on the bTAML framework. Changing the substituents from OMe to NO2 resulted in an eightfold increase in reaction rate, while the overpotential increased threefold.

Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini (New Journal of Chemistry, 2017)
The extent of alloying and the alloy composition, which are crucial in determining the activity and selectivity of bimetallic catalysts, were studied in porous silica encapsulated AgPd catalysts using XRD, HRTEM and HAADF-STEM. Water-dispersible ligand protected Pd ultra-small clusters and Ag nanoparticles of three different sizes were used as the precursors. The high reactivity of Pd ultra-small clusters enhanced the alloying of larger Ag nanoparticles to some extent. Encapsulation appeared to have minimised the sintering of the resultant nanoparticles. The earlier suggestions of the role of d-band positions with respect to adsorption energies holds good for the AgPd system and alloying enhances the activity. Alloy with the composition of Ag50Pd50 was found to be the most active with the reaction rate enhanced two fold compared to that in other compositions. Other factors like particle size and sinter-resistance also played important roles in enhancing the activity of these catalysts.

Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties (vol 41, pg 14652, 2017) - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini (New Journal of Chemistry, 2020)